The copper spoil heap Knappenberg, Austria, as a model for metal habitats – Vegetation, substrate and contamination - Adlassnig, Wolfram; Weiss, Yasmin S.; Sassmann, Stefan; Steinhauser, Georg; Hofhansl, Florian; Baumann, Nils; Lichtscheidl, Irene; Lang, Ingeborg (Science of the Total Environment, 2016)
Historic mining in the Eastern Alps has left us with a legacy of numerous spoil heaps hosting specific, metal tolerant vegetation. Such habitats are characterized by elevated concentrations of toxic elements but also by high irradiation, a poorly developed substrate or extreme pH of the soil. This study investigates the distribution of vascular plants, mosses and lichens on a copper spoil heap on the ore bearing Knappenberg formed by Prebichl Layers and Werfener Schist in Lower Austria. It serves as a model for discriminating between various ecological traits and their effects on vegetation. Five distinct clusters were distinguished: (1) The bare, metal rich Central Spoil Heap was only colonised by highly resistant specialists. (2) The Northern and (3) Southern Peripheries contained less copper; the contrasting vegetation was best explained by the different microclimate. (4) A forest over acidic bedrock hosted a vegetation overlapping with the periphery of the spoil heap. (5) A forest over calcareous bedrock was similar to the spoil heap with regard to pH and humus content but hosted a vegetation differing strongly to all other habitats. Among the multiple toxic elements at the spoil heap, only Cu seems to exert a crucial influence on the vegetation pattern. Besides metal concentrations, irradiation, humidity, humus, pH and grain size distribution are important for the establishment of a metal tolerant vegetation. The difference between the species poor Northern and the diverse Southern Periphery can be explained by the microclimate rather than by the substrate. All plant species penetrating from the forest into the periphery of the spoil heap originate from the acidic but not from the calcareous bedrock. © 2016 Elsevier B.V.
Keywords: Copper; Ecosystems; Forestry; Grain Size And Shape; Irradiation; Metals; Ores; Soils; Ecological Traits; Elevated Concentrations; Grain Size Distribution; Metal Concentrations; Metal Tolerance; Metallophytes; Ore Minerals; Vegetation Pattern; Vegetation; Copper; Copper; Copper; Lichen; Moss; Ore Mineral; Pollution Tolerance; Spoil Heap; Vascular Plant; Vegetation; Air Temperature; Austria; Contamination; Controlled Study; Environmental Aspects And Related Phenomena; Humidity; Lichen (organism); Metal Tolerance; Microclimate; Moss; Nonhuman; Plant Growth; Priority Journal; Sensitivity Analysis; Soil Acidity; Species Distribution; Species Richness; Spoil Heap; Vascular Plant; Vegetation; Chemistry; Drug Effects; Ecosystem; Forest; Growth, Development And Aging; Metabolism; Mining; Soil; Soil Pollutant; Alps; Austria; Eastern Alps; Lower Austria; Bryophyta; Tracheophyta; Austria; Bryophyta; Copper; Ecosystem; Forests; Lichens; Mining; Soil; Soil Pollutants; Tracheophyta